Toddlerhood and Preschool Age: The Dynamics of Early Childhood Development - Rzechowska, Ewa (Social and Personality Development in Childhood, 2025)
With the rapid development of motor skills in early childhood, the child’s perception, attention and memory improve, and preoperational thinking replaces thinking in action. The changes influence the child’s logic, reasoning, and understanding of the world. Also, in early childhood, the child’s theory of mind takes shape as the child tries to understand others’ states of mind and feelings.Toddlerhood and the preschool years involve the development of the child’s individuality, autonomy, initiative, self-esteem and self-evaluation, as well as the formation of autobiographical memory and gender identity.Increasing self-awareness, understanding of people’s expectations and the emergence of a conscience let the child compare his or her behaviour against the established rules, prompting the birth of emotional states (shame, pride and guilt) and the ability to regulate them. The emerging awareness of norms and standards stimulates moral development. At its early stage (the pre-conventional level), the child makes judgments dictated by his or her practical interests and the need to avoid trouble, even if the child has a sense of the needs of others.By around the age of three, children acquire the basics of their native language, leading to the development of their vocabulary, grammar and communication skills.During the early years of life, children adopt behavioural patterns within the family (primary socialisation). These patterns are later applied outside the family and enriched through interactions with peers and teachers in kindergartens and other care settings (secondary socialisation). Peers and early friendships play a significant role in a child’s socialisation, as does the evolving social organisation of play—from unoccupied play to cooperative play—and the development of prosocial behaviours.The skills and abilities acquired during early childhood are essential for a child’s successful adaptation to the school environment.Keywords: toddlerhood, preschool age, pre-operational thinking, personality development, moral judgment, emotional development, communication skills, primary and secondary socialisation